2017
DOI: 10.1016/j.jmb.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 Is a Modular, Scaffolding Protein that physically Links Heat Shock Protein 70 (Hsp70) to the Small Heat Shock Proteins

Abstract: Small heat shock proteins (sHsps) are a family of ATP-independent molecular chaperones that are important for binding and stabilizing unfolded proteins. In this task, the sHsps have been proposed to coordinate with ATP-dependent chaperones, including heat shock protein 70 (Hsp70). However, it isn’t yet clear how these two important components of the chaperone network are linked. We report that the Hsp70 co-chaperone, BAG3, is a modular, scaffolding factor to bring together sHsps and Hsp70s. Using domain deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 66 publications
6
133
0
Order By: Relevance
“…This stringent cutoff yielded 123 potential binding partners. Interestingly, several ATPase-independent sHSP family members (HSPB5, -6, and -8), and ATPase-dependent HSP70 family members (HSP70 and HSC70), previously identified as part of the BAG3 complex (35), were among the 123 potential binding partners identified in this manner. Notably, of the 123 potential binding partners, 39 were overlapping with proteins identified as being increased within the insoluble protein fraction from BAG3-CKO hearts ( Figure 4, B and C, Figure 3, B and E, and Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…This stringent cutoff yielded 123 potential binding partners. Interestingly, several ATPase-independent sHSP family members (HSPB5, -6, and -8), and ATPase-dependent HSP70 family members (HSP70 and HSC70), previously identified as part of the BAG3 complex (35), were among the 123 potential binding partners identified in this manner. Notably, of the 123 potential binding partners, 39 were overlapping with proteins identified as being increased within the insoluble protein fraction from BAG3-CKO hearts ( Figure 4, B and C, Figure 3, B and E, and Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…Notably, the BAG3 E455K mutation did not affect BAG3 binding to sHSPs ( Figure 5C) (35). Taken together, we concluded that the ability of BAG3 to interact with HSP70 was essential to the stability of sHSPs.…”
Section: 9mentioning
confidence: 71%
See 2 more Smart Citations
“…As a co-chaperone, the BAG3 protein modulates ATP turnover and the protein folding activity of HSC70 (constitutive) and HSP70 (induced) (18,19). It also physically and functionally interacts with a separate family of chaperones, the small heat shock proteins (HSPB genes), and acts as a scaffold that links the functions of HSP70 and HSPB families (20)(21)(22). In human cells, the BAG3-HSP70-HSPB complex regulates degradation of ubiquitinated proteins via the proteasome and autophagy pathways (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%